Faktor Determinan Rutur Perineum Derajat I dan III - Erni Dwi Widyana; Afnani Toyibah; Siti Martina (Malang Journal of Midwifery (MAJORY), 2019)
Postpartum hemorrhage reaches 50% in Indonesia in 2010. postpartum hemorrhage is an important cause of maternal mortality, especially in developing countries. The things that cause postpartum hemorrhage was atonic uterus, birth canal injury, the release of part of the placenta from the uterus, such as the lagging portion of the placenta or placenta suksenturiata cotyledons. Injury in the birth canal that cause a lot of bleeding is the rupture of the perineum. The research objective was to determine the determinant factors which affect the rupture of the perineum in BPM "I" Malang. The study design was analytic correlation with cross sectional approach. A population of 35 people and the number of samples of 35 people by using total sampling. Collection of data using interviews and observation sheet. Based on logistic regression test showed that the 0.05 sign of the determinant factors including parity, maternal age, duration of the second stage, and the weight of newborns only the most determinant parity against rupture perineum. Expected health workers more attention in providing services intranatal care so as to prevent and reduce the incidence of ruptured perineum. Keywords: Determinant Factors, Rupture perineum